A310 DAILY ADMINISTRATION OF LACTOBACILLUS PLANTARUM IMPROVES MOUSE JUVENILE GROWTH KINETICS BY SUSTAINING SOMATOTROPIC AXIS ACTIVITY UPON UNDERNUTRITION. (1st March 2018) - Schwarzer, M; Poinsot, P; Lambert, A; Goeffroy, S; Peretti, N; Leulier, F
Abstract: Background: Chronic undernutrition, a condition currently affecting more than 17 millions of children under five years of age, has severe long-term consequences including stunting. Epidemiologic studies have emphasized that undernutrition cannot be ascribed to food insecurity alone and gut microbiota has been shown to play an active role in disease aetiology. In mammals, post-natal growth is controlled by the activity of the somatotropic axis. Undernutrition leads to a decrease of the Insulin like Growth Factor 1 (IGF-1) and a state of Growth Hormon (GH) resistance. Aims: Previously we have shown the capacity of selected Lactobacillus plantarum strain to maintain growth in infant mono-colonized mice during chronic undernutrition. Here we show that L. plantarum retains its growth promoting capabilities also in a conventional mouse model. Methods: C57BL6 male mice were weaned at 21 days and bred on a standard or an experimental (isocaloric, hypoprotidic and hypolipidic) diet until young adulthood. One group of mice on experimental diet received an Lp WJL oral supplementation (2*10^8 CFU/day; 5 days per week) and the other group received placebo. Length and weight were measured weekly. Mice were sacrificed at day 56 to study the impact of the Lp WJL oral supplementation on IGF-1 levels and organ growth. Somatotropic axis activity was tested at Day 28 by injecting the mice with GH and measured by the STAT5 phosphorylation level. Results: At D56, mice fed with the experimental diet were smaller than the standard diet group (7.7 vs 8.9 cm; p< 0.01). Undernourished mice had a lower hepatic level of IGF-1 (113 ± 39 vs 174 ± 35 pg/mg tissues; p<0.01) and a lower plasmatic level of IGF-1 (150 ± 50 vs 388 ± 103 ng/mL; p< 0.01) compared with the standard diet group. Body length of mice fed experimental diet was longer in Lp WJL –supplemented group compared to the placebo supplementation (8.02 ± 0.19 vs 7.73 ± 0.16 cm; p<0.0001). Lp WJL -treated mice showed 23% increase in daily growth gain compared to placebo without the change in the mean daily food intake. In the Lp WJL group, mice had a higher hepatic IGF-1 level (108 ± 12.5 vs 59.8 ± 18.5 pg/mg tissues; p< 0.0001) and a higher plasmatic IGF-1 level (209 ± 51 vs 148 ± 32 ng/mL; p< 0.001) compared to the placebo group. At day 28, mice exposed to Lp WJL during starvation process showed an increase of the sensibility of the hepatic GH receptor to GH according to the STAT5 phosphorylation level. Conclusions: Oral supplementation by Lp WJL alleviates the GH resistance and improves juvenile growth of conventional infant mice upon undernutrition. Funding Agencies: None